2006
DOI: 10.1007/s00418-006-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of extracellular matrix proteins type I collagen, type IV collagen, fibronectin, and laminin in mouse folliculogenesis

Abstract: The extracellular matrix (ECM) plays a prominent role in ovarian function by participating in processes such as cell migration, proliferation, growth, and development. Although some of these signaling processes have been characterized in the mouse, the relative quantity and distribution of ECM proteins within developing follicles of the ovary have not been characterized. This study uses immunohistochemistry and real-time PCR to characterize the ECM components type I collagen, type IV collagen, fibronectin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
122
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 41 publications
12
122
0
Order By: Relevance
“…We previously proposed that granulosa-derived CTGF is one of the main signals for formation of the thecal compartment when follicles form and begin to grow. A continuing role for CTGF in the extensive thecal remodelling required during antral stages of follicular development seems equally likely, particularly in light of the recent finding that key ECM markers, such as collagen IV and fibronectin appear to be developmentally regulated in the mouse follicle (Berkholtz et al 2006). In this connection, CTGF is implicated in the deposition of collagen, through its role in modulating lysyl oxidase (Hong et al 1999), a crucial enzyme required for cross-linking of collagen monomers (Smith-Mungo & Kagan 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously proposed that granulosa-derived CTGF is one of the main signals for formation of the thecal compartment when follicles form and begin to grow. A continuing role for CTGF in the extensive thecal remodelling required during antral stages of follicular development seems equally likely, particularly in light of the recent finding that key ECM markers, such as collagen IV and fibronectin appear to be developmentally regulated in the mouse follicle (Berkholtz et al 2006). In this connection, CTGF is implicated in the deposition of collagen, through its role in modulating lysyl oxidase (Hong et al 1999), a crucial enzyme required for cross-linking of collagen monomers (Smith-Mungo & Kagan 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian CTGF immunoreactivity has previously only been observed in the pig (Wandji et al 2000), where it paralleled mRNA expression in granulosa, theca and vascular endothelial cells of the theca and corpus luteum. Several ECM components have been characterised during mouse follicular development (Berkholtz et al 2006). For example, fibronectin and type IV collagen are detectable in theca, stroma and basement membrane of small preantral (SP) follicles and increase as the follicle size increases (Berkholtz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring extracellular matrices such as fibronectin, laminin, and collagen are deposited in ovarian follicles during follicle development. These matrices have important functions in a stage-specific manner (Berkholtz et al 2006). In this study, we focused on collagen gel, because collagen has been reported to stimulate cell growth and development in various mammalian cell culture systems (Wicha et al 1979, Yang et al 1980, Yang & Nandi 1983.…”
Section: Introductionmentioning
confidence: 99%
“…This discriminatory divider is comprised mainly of collagen and laminin (Rodgers et al 1999;Berkholtz et al 2006) and allows only molecules of a certain size and charge to cross (Hess et al 1998). The FBL changes with the developing follicle, adapting its permeability and constituent molecules.…”
Section: Introductionmentioning
confidence: 99%